Advancement toward polymer electrolyte membrane fuel cells at elevated temperatures - Zhang, J.; Aili, D.; Lu, S.; Li, Q.; Jiang, San Ping (AMER ASSOC ADVANCEMENT SCIENCE, 2020)
Elevation of operational temperatures of polymer electrolyte membrane fuel cells (PEMFCs) has been demonstrated with phosphoric acid-doped polybenzimidazole (PA/PBI) membranes. The technical perspective of the technology is simplified construction and operation with possible integration with, e.g., methanol reformers. Toward this target, significant efforts have been made to develop acid-base polymer membranes, inorganic proton conductors, and organic-inorganic composite materials. This report is devoted to updating the recent progress of the development particularly of acid-doped PBI, phosphate-based solid inorganic proton conductors, and their composite electrolytes. Long-term stability of PBI membranes has been well documented, however, at typical temperatures of 160 C. Inorganic proton-conducting materials, e.g., alkali metal dihydrogen phosphates, heteropolyacids, tetravalent metal pyrophosphates, and phosphosilicates, exhibit significant proton conductivity at temperatures of up to 300 C but have so far found limited applications in the form of thin films. Composite membranes of PBI and phosphates, particularly in situ formed phosphosilicates in the polymer matrix, showed exceptionally stable conductivity at temperatures well above 200 C. Fuel cell tests at up to 260 C are reported operational with good tolerance of up to 16% CO in hydrogen, fast kinetics for direct methanol oxidation, and feasibility of nonprecious metal catalysts. The prospect and future exploration of new proton conductors based on phosphate immobilization and fuel cell technologies at temperatures above 200 C are discussed.